The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1103/physrevb.104.035408
|View full text |Cite
|
Sign up to set email alerts
|

Fermiology of two-dimensional titanium carbide and nitride MXenes

Abstract: MXenes are a family two-dimensional transition-metal carbide and nitride materials, which often exhibit very good metallic conductivity and are thus of great interest for applications in, e.g., flexible electronics, electrocatalysis, and electromagnetic interference shielding. However, surprisingly little is known about the fermiology of MXenes, i.e., the shape and size of their Fermi surfaces, and its effect on the material properties. One reason for this may be that MXene surfaces are almost always covered b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 40 publications
(59 reference statements)
0
13
0
Order By: Relevance
“…Here, τ 0 is the relaxation time, and d is the interlayer spacing. For all calculations, we are assuming τ 0 to be 1 fs as it gives the value of conductivity close to experimental reports . The values of d taken from experiments are 7.7 Å for Ti 2 CT z and 9.16 Å for Mo 2 CT z .…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…Here, τ 0 is the relaxation time, and d is the interlayer spacing. For all calculations, we are assuming τ 0 to be 1 fs as it gives the value of conductivity close to experimental reports . The values of d taken from experiments are 7.7 Å for Ti 2 CT z and 9.16 Å for Mo 2 CT z .…”
Section: Resultsmentioning
confidence: 78%
“…Within the constant relaxation time approximation, the sheet conductivity of a 2D material can be calculated with the knowledge of the average Fermi velocity and Fermi surface area. The detailed methodology is presented by M. Bagheri et al in their Supporting Information. The final expression for sheet conductivity of MXene is given by ( σ 2 normalD τ 0 ) = e 2 2 π 2 false⟨ v F false⟩ 2 l F where ℏ is the reduced Planck’s constant, l F is the Fermi surface length ( l F = a normalF b z and b z = 2 π L z : a F , Fermi surface area and L z , length of unit cell in the z -direction), and ⟨ v F ⟩ is the average Fermi velocity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanism 2 can dominate over mechanism 1 in the case of H 2 S and NH 3 for which the adsorption energy is comparable or higher than that of H 2 O. In order to estimate how the charge transfer would affect resistance, instead of ballistic conductance calculations, , we here rely on ref where it was computationally shown that when O content of Ti 3 C 2 T x surfaces is more than 50%, an increasing electron concentration (positive charge transfer from the analyte) leads to increasing conductivity and thereby a negative sensor response, as is the case with H 2 S.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanism 2 can dominate over mechanism 1 in the case of H 2 S and NH 3 for which the adsorption energy is comparable or higher than that of H 2 O. In order to estimate how the charge transfer would affect resistance, instead of ballistic conductance calculations, 57,58 we here rely on ref 59 where it was computationally shown that when O content of Ti 3 C 2 T x surfaces is more than 50%, an increasing electron concentration (positive charge transfer from the analyte) leads to increasing conductivity and thereby a negative sensor response, 59 as is the case with H 2 S. The response of NH 3 is more complicated, which makes it difficult to draw firm conclusions based on the calculations. Because NH 3 captures H + and 0.29e from MXenes, and H atoms in the OH group contains about 0.8e, 0.51e remains in the MXene and the response should be in the same direction as with H 2 S, in contrast to the experiments.…”
Section: H 2 S Gas Sensing Mechanismmentioning
confidence: 99%